Quantum mechanics versus equivalence principle - Accioly, Antonio [UNESP]; Paszko, Ricardo (American Physical Society (APS), 2008)
We consider the scattering of a photon by a weak gravitational field, treated as an external field, up to second order of the perturbation expansion. The resulting cross section is energy dependent which indicates a violation of Galileo's equivalence principle (universality of free fall) and, consequently, of the classical equivalence principle. The deflection angle θ for a photon passing by the sun is evaluated afterward and the likelihood of detecting ΔθθE≡θ-θEθE (where θE is the value predicted by Einstein's geometrical theory for the light bending) in the foreseeable future, is discussed. © 2008 The American Physical Society.